Causes, Predisposing Factors and Prevention Directions of Drug-induced Bradycardia (Based on the Results of the Hospital Register of Oardiac Medications Overdoses STORM) - N. N. Nikulina; S. V. Seleznev; M. B. Chernysheva; S. S. Yаkushin (Рациональная фармакотерапия в кардиологии, 2021)
Aim. Analysis of drug-induced bradiarrhythmia (DIB) causes and predisposing factors, followed by the development of recommendations for practitioners on its prevention.Material and methods. The register included consistently all cases of hospitalization at the Regional Vascular Center (Ryazan) due to DIB in 2017 (n=114), 2018 (n=167), and retrospectively in 2014 (n=44). In total, 325 cases were reported: men - 26.1%, age 76.0 [68.0; 82.0] years; patients >65 years - 83.7%, and patients >75 years - 57.9%. The dose of medications with bradycardic action (BCA) taken the day before was known in 227 cases (69.8%), which allowed us to analyze the correctness of the intake regime in these cases.Results. The excess of a single and / or daily medication dose (absolute overdose, AOD) occurred only in 10.6% of cases and was associated with the patient's attempt to cope with the deterioration of the disease or an acute clinical situation on their own. In other cases, there was no formal violation of the Instructions, but there was an inhibition of the heart's conducting system activity, characteristic of an overdose of medication (the so-called "relative” overdose, ROD). It was due to the summation/potentiation of BCA of several medications or changes in the medication pharmacokinetics. There were no differences in the clinical and demographic characteristics of patients and the provision of medical care in the groups with AOD and ROD (p>0.05). The exception was a high frequency of bradycardia <40 beats / min in AOD group (75.0% vs 49.8%, p=0.019) and, as a result, - management in the conditions of the Intensive Care Unit (66.7% vs 39.9%, p=0.012). Frequency of pre-admission receiving medications in AOD and ROD groups also did not differ (p>0.05): beta-blockers - an average of 64.3%, antiarrhythmic drugs with BCA- 41.0%, cardiac glycosides 25.1% (frequency each of these medicationsin DIB cases over the 5-year period has not changed), an agonist of the 11-imidazoline receptors - moxonidine (12.3%, its frequency has increased 8.9 times in 5 years, p=0.004), non-dihydropyridine calcium antagonists - 7.9% (decrease frequency over 5 years 4.0 times, p=0.002), other - 16.7%. In 56.8% of cases, medications with BCA were used in combination. At admission, a decrease in glomerular filtration rate (GFR) <45 ml/min/1.73 m2 was registered in 56.8% of cases, <30 ml/min/1.73 m2 - in 31.8%, <15 ml/min/1.73 m2 -in 10.9% (differences between groups with p>0.05). Hospital lethality in the AOD group is 4.2%, in the ROD group- 5.4% (p>0.05).Conclusion. The main reasons of DIB are excess of the recommended dose, unrecorded summation/potentiation of BCA of several medications, and / or changes in the medication pharmacokinetics. Predisposing factors are self-medication of patients with worsening cardiovascular disease or acute clinical situations (e.g., hypertensive crisis), taking multiple medications with BCA, accession of heart disease, manifested by bradyarrhythmia, decrease in GFR, elderly and senile age.